Significant displacement of calcium and barium ions in ferroelectric (Ba0.9Ca0.1)TiO3 revealed by x-ray fluorescence holography - Yamamoto, Y.; Kawamura, K.; Sugimoto, H.; Gadelmawla, Ahmed; Kimura, K.; Happo, N.; Tajiri, H.; Webber, Kyle Grant; Kakimoto, K.; Hayashi, K. (Applied Physics Letters, 2022)
The x-ray fluorescence holography technique is applied to perovskite (Ba0.9Ca0.1)TiO3 ferroelectrics in order to investigate the local structures around the Ca and Ba ions at the A-site. While the A-site atomic images around the Ba ion can be well understood based on the BaTiO3 structure, those around the Ca ion are located at the closer positions to the emitter. Furthermore, the shape of the atomic image around the Ca ion is elongated in the radial direction. These features clearly show the local lattice contraction around the Ca ion and a significant displacement of the Ca ions from the ideal position. On the basis of the detailed analysis of the position and the shape of the atomic image around the Ca ion, it is found that the Ca ions are displaced by & SIM;0.36 & ANGS; in the & lang; 111 & rang; direction, and the surrounding Ba ions are displaced by & SIM;0.22 & ANGS; in the & lang;100 & rang; direction. The present results indicate that the doped Ca ions activate the A-site polarization of this compound, which can lead to an enhancement of the ferroelectric and piezoelectric performances.
CRIS-Team WoS Importer:2022-02-11